Molecular and Phylogenetic Study of The H P A I (High Pathogenic Avian Influenza) Virus Sub-type H5N8 in Iraq (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Avian influenza (AI) is aspreadableinfection of the birds and humans affected by type A of influenzavirus. Highly pathogenic avian influenza (HPAI) caused by the viruses subtype (H5N1) and (H5N8) isconsider as a definite risk to the poultry industry and human health and it is started as the occasionalrevolutionize a satisfactory because of migratory bird which consider as a carrier of the disease. Twentyoropharyngeal swabs were collected from infected flock have suffer from sudden death with high mortality,all these samples were collected from (1-5) days after clinical signs appears and the results summarized bythree farms infected with HPAI subtype (H5N8), three viral isolates strain out of 20 samples were identifiedby RT-PCR assay, two of them have layer origin while one have broiler origin, the three sequencing resultsin this study have been presented to the gene bank database under accession number MN689674.1 andMN658854.1, phylogenetic analysis of our sequences were used to relatedness of strain obtaining with otheravian influenza viruses around the world, the a current sequences of avian H5N8 strains were found to berelated as a common ancestor with Iranian registered strain.